The substrate binding domains of human SIAH E3 ubiquitin ligases are now crystal clear - Zhang, Qi; Wang, Zhongduo; Hou, Feng; Harding, Rachel; Huang, Xinyi; Dong, Aiping; Walker, John R.; Tong, Yufeng (Biochimica et biophysica acta. General subjects, 2017)
Seven in absentia homologs (SIAHs) comprise a family of highly conserved E3 ubiquitin ligases that play an important role in regulating signalling pathways in tumorigenesis, including the DNA damage repair and hypoxia response pathways. SIAH1 and SIAH2 have been found to function as a tumour repressor and a proto-oncogene, respectively, despite the high sequence identity of their substrate binding domains (SBDs). Ubiquitin-specific protease USP19 is a deubiquitinase that forms a complex with SIAHs and counteracts the ligase function. Much effort has been made to find selective inhibitors of the SIAHs E3 ligases. Menadione was reported to inhibit SIAH2 specifically. We used X-ray crystallography, peptide array, bioinformatic analysis, and biophysical techniques to characterize the structure and interaction of SIAHs with deubiquitinases and literature reported compounds. We solved the crystal structures of SIAH1 in complex with a USP19 peptide and of the apo form SIAH2. Phylogenetic analysis revealed the SIAH/USP19 complex is conserved in evolution. We demonstrated that menadione destabilizes both SIAH1 and SIAH2 non-specifically through covalent modification. The SBDs of SIAH E3 ligases are structurally similar with a subtle stability difference. USP19 is the only deubiquitinase that directly binds to SIAHs through the substrate binding pocket. Menadione is not a specific inhibitor for SIAH2. The crystallographic models provide structural insights into the substrate binding of the SIAH family E3 ubiquitin ligases that are critically involved in regulating cancer-related pathways. Our results suggest caution should be taken when using menadione as a specific SIAH2 inhibitor. •Crystal structures of apo-SIAH2 and USP19/SIAH1 complex are solved.•USP19 is the only deubiquitinase found to bind with SIAH E3 ubiquitin ligases.•The USP19/SIAH complex is conserved in evolution.•Menadione destabilizes both SIAH1 and SIAH2 non-specifically.